THE EFFECT OF U-TURN ON TRAFFIC FLOW CHARACTERISTICS (A CASE STUDY: JENDRAL BASUKI RACHMAT ROAD, EAST JAKARTA) - Basit Al Hanif; Noviandi Putra Darsono (University Of Muhammadiyah Jakarta, 2022)
The way to minimize traffic problems, especially the safety and comfort of roads is to build medians. The median as part of the road geometry is a physical separator of traffic lanes that serves to relieve traffic conflicts from the opposite direction. So, it improves traffic safety with a reversal facility, analyzes the average travel time of vehicles when making a U-turn, and analyzes the level of service on the Jendral Basuki Rachmat road. Therefore, this research aimed to determine the volume of traffic on Jenderal Basuki Rachmat road, determine the average speed of turning vehicles and determine the service level on Jalan Jenderal Basuki Rachmat Road. This research used the 1997 MKJI methodology. The research results explained that the largest volume of vehicles that make U-turns was 19966 vehicles/hour with a road service level of D. The average travel time of vehicles was 15.3 seconds with a queue length of 50 meters for a U-turn.